2018
DOI: 10.3389/fnins.2018.00797
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Fraction Amplitude of Low Frequency Fluctuation at Resting State in Patients With Early Left and Right Bell’s Palsy: Do They Have Differences?

Abstract: Purpose: Bell’s palsy refers to acute idiopathic unilateral facial nerve palsy. It is a common disorder of the main motor pathway to the facial muscles. This study aimed to investigate the abnormal fraction amplitude of low frequency fluctuation (fALFF) of the brain in patients with early left and right Bell’s palsy.Materials and Methods: Sixty-seven patients (left 33, right 34) and 37 age- and sex-matched healthy controls underwent resting-state functional magnetic resonance imaging (R-fMRI) examination. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…However, our results are consistent with the result of an earlier study that reported blocking facial mimicry of healthy subjects causes different neural activations in the amygdala in response to emotional stimuli [3]. Our results are also compatible with a very recent study that compared patients with facial nerve paralysis and healthy controls in resting state and found that the brain fraction amplitude of low-frequency fluctuation is abnormal in emotion-related regions [46].…”
Section: Discussionsupporting
confidence: 93%
“…However, our results are consistent with the result of an earlier study that reported blocking facial mimicry of healthy subjects causes different neural activations in the amygdala in response to emotional stimuli [3]. Our results are also compatible with a very recent study that compared patients with facial nerve paralysis and healthy controls in resting state and found that the brain fraction amplitude of low-frequency fluctuation is abnormal in emotion-related regions [46].…”
Section: Discussionsupporting
confidence: 93%
“…changes in local and distal FC (Zhou, Shi, et al, 2019; Zhou, Tang, et al, 2019). Alterations, mostly increases, in fALFF values in a spectrum of pathological states (Du et al, 2019; Han et al, 2018; Zeng et al, 2019; Zhou, Tang, et al, 2019) suggest fairly good sensitivity but not necessarily neurobiological specificity. Indeed, abnormalities in cortical fALFF patterns can also be observed in subjects with white matter lesions, such as in Bell's palsy (Han et al, 2018), suggestive of reactive changes of neural firing patterns to altered whole network function.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations, mostly increases, in fALFF values in a spectrum of pathological states (Du et al, 2019; Han et al, 2018; Zeng et al, 2019; Zhou, Tang, et al, 2019) suggest fairly good sensitivity but not necessarily neurobiological specificity. Indeed, abnormalities in cortical fALFF patterns can also be observed in subjects with white matter lesions, such as in Bell's palsy (Han et al, 2018), suggestive of reactive changes of neural firing patterns to altered whole network function. Furthermore, there are reports of distinct fALFF patterns associating with personality traits in healthy individuals (Ikeda et al, 2017; Wei et al, 2011) and mathematical disability in children (Jolles et al, 2016), advocating an interpretation for fALFF as a nonspecific marker of altered neural activity in a neural population.…”
Section: Discussionmentioning
confidence: 99%
“…These regions with altered FC further highlight the differences in functional reorganization activities, mainly involving the emotional processes network in the right palsy group, and motor-related functional integration in the left palsy group, compared to the healthy controls. We speculate that psychological stress and negative emotions are heightened to different degrees in patients with bilateral Bell's palsy, because of their involuntary abnormal facial expressions and movements (30).…”
Section: Discussionmentioning
confidence: 92%